Strategic orientation in change management and using it when designing the company's development strategy = Strategiczna orientacja zarządzania zmianami i jej wykorzystanie w procesie projektowania rozwoju przedsiębiorstwa - Skalik, Jan (Zielona Góra: Faculty of Economics and Management Press)
Designing the company's development program is a complex project in which it is necessary to preserve the logical sequence of analytical actions but also to respect the basic factors defining the correct direction and program of changes. The article presents the structure of related design actions as well as the strategic aspects of building a program of development changes in the company resulting not only from its general strategy but also from the adopted pattern of development and the change management strategy.
Keywords: przedsiębiorstwo; rozwój przedsiębiorstwa; program rozwoju; ogólna strategia firmy; zarządzanie zmianami; kumulacja strategiczna; enterprises; development of company; development programs; company's general strategy; change management; strategic accumulation